2001
DOI: 10.1111/j.1398-9995.2001.00911.x
|View full text |Cite
|
Sign up to set email alerts
|

Dog allergen in indoor air and dust during dog shows

Abstract: Proteins (CMP) involved in milk allergy are numerous and heterogeneous, with very few structural or functional common features. This heterogeneity is complicated by their genetic polymorphism, resulting in several variants for each protein. These variants are characterized by point substitutions of amino acids or by deletions of peptide fragments of varying size or by post-translational modifications such as phosphorylation or glycosylation. All of these modifications may affect allergenicity. No common molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
66
0
4

Year Published

2006
2006
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(70 citation statements)
references
References 36 publications
0
66
0
4
Order By: Relevance
“…The allergen was thought to be casein, β-lactoglobulin, or both. They are major heat-resistant milk allergens, and ingestion of products such as pasta with cream sauce, cheese, or dairy-based ice cream could induce allergic reactions [28]. It is possible that EGE has various pathogenic mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…The allergen was thought to be casein, β-lactoglobulin, or both. They are major heat-resistant milk allergens, and ingestion of products such as pasta with cream sauce, cheese, or dairy-based ice cream could induce allergic reactions [28]. It is possible that EGE has various pathogenic mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Ena et al (1995) found that a filter with molecular mass cut-off 3,000 Da decreased residual antigenicity of the Corolase 7092 WPC hydrolysate, but had little effect on the pepsin/carolase PP hydrolysate. Peptides still have allergenicity if epitopes exist, although their molecular masses may be very low (Wal 2001). This result suggests that it is crucial to choose the appropriate enzyme having specificities in antigenic epitopes to effectively decrease the allergenicity of proteins.…”
Section: Enzymatic Hydrolysismentioning
confidence: 99%
“…The resistance of b-Lg to digestion, particularly in the gastric compartment, coupled with its absence from human milk has been proposed to contribute to the allergenicity of bovine b-Lg in human [16]. Several other allergens belonging to the lipocalin family have also been identified, including inhalant allergens such as mouse urinary protein, and several dander allergens [17].…”
Section: Introductionmentioning
confidence: 99%